2017
DOI: 10.1002/mnfr.201601061
|View full text |Cite
|
Sign up to set email alerts
|

Is mealworm or shrimp allergy indicative for food allergy to insects?

Abstract: Shrimp allergic patients are most likely at risk of food allergy to mealworm and other insects. Primary mealworm allergy does not mean subjects are likely to react to all insects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 24 publications
3
80
1
Order By: Relevance
“…India also showed the highest percentage of people (75%) Indeed, more studies are necessary to prove that insects are allergens or not. According to Broekman et al (2017), shrimp allergic patients are most likely at risk of food allergy to mealworm and other insects.…”
Section: External Variablesmentioning
confidence: 99%
“…India also showed the highest percentage of people (75%) Indeed, more studies are necessary to prove that insects are allergens or not. According to Broekman et al (2017), shrimp allergic patients are most likely at risk of food allergy to mealworm and other insects.…”
Section: External Variablesmentioning
confidence: 99%
“…For instance, Broekman et al . () studied the allergenic potential of seven edible insects, i.e. T. molitor, H. illucens , A. domesticus , the giant mealworm, Zophobas morio (F.) (Coleoptera: Tenebrionidae), the large wax moth, Galleria melonella (L.) (Lepidoptera: Galleridae), the variegated grasshopper Zonocerus variegatus (L.) (Orthoptera: Pyrgomorphidae), as well as A. diaperinus , and suggested that shrimp allergic population is most likely at risk of food allergy to A. diaperinus and the rest of the insects tested.…”
Section: Public Health Concerns – Safety Issuesmentioning
confidence: 99%
“…In a double‐blind placebo‐controlled food challenge (DBPCFC) study with 15 shrimp‐allergic patients, clinically relevant co‐sensitization to mealworm in 13 could be detected . Co‐sensitization to cricket, giant mealworm, lesser mealworm, grasshopper, wax moth and black soldier fly could be demonstrated in vitro in 15 shrimp‐allergic patients . In some cases, allergic reactions occurred upon first ingestion, suggestive of cross‐sensitization, for example via shrimp .…”
Section: Allergies To Ingested Insectsmentioning
confidence: 99%
“…Double‐blind placebo‐controlled food challenge was previously used to diagnose food allergy to mealworm . Most other studies used IgE‐binding tests such as immunoblot, ELISA or radioallergosorbent test (RAST), or functional skin prick tests and BAT with extracts of insects.…”
Section: Allergies To Ingested Insectsmentioning
confidence: 99%